Does Cost Influence the Choice of Disposable vs Reusable Instruments? Survey of Obstetrician/Gynecologists [24Q]. (May 2018) - Yang, Helen; Ross, Sue; Capstick, Valerie
Abstract : INTRODUCTION: A "cost awareness" campaign was undertaken at the Lois Hole Hospital for Women from 2015 to 2016 to raise awareness about costs of disposable versus reusable instruments for laparoscopic procedures. We undertook a survey of obstetrician/gynecologists (Ob/Gyns) to find out if the campaign had affected their attitudes about choosing disposable versus cheaper reusable instruments. METHODS: In 2015 and 2017, all full-time university-associated Ob/Gyns were mailed a cover letter, questionnaire and coffee card (5) with postage-paid return envelope. Responses (with unique ID) from Ob/Gyns who perform laparoscopic procedures were entered into a password-protected REDCap database on a secure server. Data analysis used REDCap summary descriptive statistics. RESULTS: 34/47 eligible Ob/Gyns (72%) completed questionnaires before and after the intervention, with median 11.5 years in practice. The majority had undertaken MIS training, mainly during residency (78.4%) and conferences (73.0%). Before the intervention, the three most important qualities influencing their decision to use a particular instrument were safety (64.9%), effectiveness (54.1%) and personal experience (48.6%), and after the intervention were effectiveness (63.0%), safety (47.8%) and ease of use (47.8%). Device cost was ranked sixth (29.7%) before and fourth after (26.1%). CONCLUSION: Given the current economy, operative costs are constantly under review. Knowledge about Ob/Gyns' attitudes provides information to design more effective awareness campaigns to encourage use of less costly instruments. To change practice, a campaign increasing Ob/Gyns' exposure to cheaper but safe and effective instruments may help to increase uptake and potentially lead to cost reduction. Cost awareness alone is unlikely to change practice.